Entrepreneurship as Students' Career - Sandra Irawati; Tsabita Khwarazmita (Universitas Muhammadiyah Malang, 2023)
Entrepreneurial intentions and career choices cannot be divided. These two things go hand in hand when students want to start or continue a business. However, the emergence of an entrepreneurial culture should be considered when choosing an entrepreneurial career. Initially, this study undertook the idea of entrepreneurial culture as part of influencing the career choices of business and management students. The main objective of this research is to examine entrepreneurial culture's involvement in influencing the career choices of business and management students. In the research process, quantitative analysis was carried out by adopting SEM-PLS using Smart-PLS version 4.0. In the end, calculations and analysis were carried out after sorting out the completeness of the answers from students who volunteered to fill in as many as 38 people. Based on this, it was found in this study that entrepreneurial culture influences career choices by whether there is a mediation of entrepreneurial intentions. On the other hand, entrepreneurial intentions influence career choices independently.